412 First-in-human phase I/IIa trial to evaluate the safety and initial clinical activity of DuoBody®-PD-L1×4–1BB (GEN1046) in patients with advanced solid tumors. (10th December 2020) - Garralda, Elena; Geva, Ravit; Ben-Ami, Eytan; Maurice-Dror, Corinne; Calvo, Emiliano; LoRusso, Patricia; Türeci, Özlem; Niewood, Michelle; Şahin, Uğur; Jure-Kunkel, Maria; Forssmann, Ulf; Ahmadi, Tahamtan; et al.
Abstract : Background: Agonistic 4-1BB monoclonal antibodies were preclinically validated as promising cancer immunotherapies, both as monotherapy and as potentiators of the activity of PD-(L)1–blocking agents. However, toxicity and a narrow therapeutic window have hampered their clinical development. DuoBody-PD-L1×4-1BB, a first-in-class, bispecific, next-generation checkpoint immunotherapy, was designed to overcome these limitations by activating T cells through conditional 4-1BB costimulation, while simultaneously blocking the PD-L1 axis. We present preliminary data from the ongoing, first-in-human, open-label, phase I/IIa trial of DuoBody-PD-L1×4-1BB in advanced solid tumors (NCT03917381 ). Methods: During dose escalation, patients with metastatic or unresectable solid tumors not eligible for standard therapy received flat-dose DuoBody-PD-L1×4-1BB (25–1200 mg) intravenously every 3 weeks until disease progression or unacceptable toxicity. Primary endpoints were dose-limiting toxicities (DLTs) and adverse events (AEs). Secondary endpoints included pharmacokinetic parameters and antitumor activity (RECIST 1.1). Pharmacodynamic biomarkers and antitumor activity (iRECIST) were assessed as exploratory endpoints. Results: As of June 22, 2020, 61 patients were enrolled (median age: 59 years). The most common cancer types were colorectal (19.7%), ovarian (14.8%), pancreatic (9.8%), and NSCLC (9.8%). Patients had previously received a median (range) of 3 (1–11) treatments; 44.2% had prior anti-PD-(L)1 immunotherapy. Patients received a median (range) of 4 (1–15) treatment cycles; Cmax was observed shortly after the end of infusion (mean T½: 2.3–10.3 days). Maximum tolerated dose was not reached; 6 patients experienced DLTs. The most common (=10%) treatment-related AEs (all grades; grades 3–4) were transaminase elevation (24.6%; 9.8%), hypothyroidism (16.4%; 1.6%), and fatigue (13.1%; 1.6%). Treatment-related grade-3 transaminase elevations decreased upon corticosteroid administration; no treatment-related bilirubin increases or grade-4 transaminase elevations occurred. Disease control, including stable disease at first assessment and partial responses in triple-negative breast cancer, ovarian cancer, and immune checkpoint inhibitor (ICI)–pretreated NSCLC, occurred in 40/61 patients (65.6%). Pharmacologic activity, as measured by modulation of adaptive immunity mediators, was observed across a broad range of dose levels. Peripheral proliferating (Ki67+) CD8+ effector memory T cells and serum interferon-gamma levels showed maximum induction relative to baseline (p=0.01) 8 days following treatment. Conclusions: DuoBody-PD-L1×4-1BB demonstrated biologic activity and a manageable safety profile. Encouraging early clinical activity across different dose levels was observed in a heavily pretreated population with advanced solid tumors, including those resistant to prior immunotherapy or typically less sensitive to ICIs. Expansion cohorts of patients for whom DuoBody-PD-L1×4-1BB treatment could be relevant and biologically sound have started enrollment. Updated data will be presented. Acknowledgements: The authors thank Manish Gupta, Lei Pang, and Thomas Breuer at Genmab A/S; Alice Bexon, Alexander Muik, and Friederike Gieseke at BioNTech SE; and Zuzana Jirakova (formerly at BioNTech SE) for their valuable contributions. This trial was funded by Genmab A/S and BioNTech SE. Trial Registration: ClinicalTrials. gov; trial number: NCT03917381 Ethics Approval: This trial is undertaken following full approval of the final protocol, amendments, informed consent form, applicable recruiting materials, and subject compensation programs by the Independent Ethics Committee/Institutional Review Board. Consent: Written informed consent, in accordance with principles that originated in the Declaration of Helsinki 2013, current ICH guidelines including ICH-GCP E6(R2), applicable regulatory requirements, and sponsor policy, was provided by the patients.